Map of the existing research on business innovation, funding, and policy framework - Edmund Mallinguh; Zeman Zoltan (Journal of Entrepreneurship, Management and Innovation)
In the last decade, empirical studies focusing on business-related innovation, funding of innovation activities, and policy (implications) have continued to increase. However, not enough effort has been undertaken yet to investigate existing literature on the subject matter. To fill the gap, the present study seeks to synthesize and map out existing empirical studies on business innovation, financing, and policy framework published between 1990 and February 2019. Bibliographic analysis of relevant articles retrieved from the Web of Science Core Collection was performed using Vosviewer. The bibliometric results show the prominent publication outlets, authoritative scholars and items, dominant higher learning institutions, and countries. Still, selected articles were content analyzed, providing a summary of the publications, the methodology adopted, country and period covered. The papers were classified into different themes based on the study focus, thus pinpointing areas that have received more or less scholarly attention. The identified gaps from both bibliographic and content analysis offer future research opportunities in different aspects touching on business innovation, how its financed and related policy issues.